Neurological complications in patient with COVID-19 - Mishchenko, Tamara S.; Mishchenko, Vladislav M. (Psychiatry, Neurology and Medical Psychology, 2021)
The article presents an analysis of the literature, as well as our own research on neurological complications in patients with COVID-19. SARS-CoV-2 virus (further – COVID-19) damages the respiratory tract and lungs, leads to the development of not only acute heart, kidney, multiple organ failure, but also accompanied by symptoms of nervous system damage. The most common and severe among the neurological complications of COVID-19 are cerebrovascular diseases, acute necrotic encephalopathy, encephalitis, encephalomyelitis, hypoxic encephalopathy, Hyena-Barre syndrome. Studies have shown that patients with COVID-19 have an average risk of stroke of 5-8%. All subtypes of stroke can occur as a result of infection. Recommendations for the management of stroke patients with COVID-19 are presented. Lesions of the peripheral nervous system are manifested in the form of hyposmia, anosmia, Hyena-Barre syndrome. An association between the severity of the viral infection and the frequency and severity of neurological disorders has been established. The results of own researches of 42 patients in the postcovid period are presented. It was shown that 95.2% of patients had neurocognitive disorders of varying severity, asthenic syndrome (increased fatigue on the MF1-20 scale 13.0 points), sleep disorders, dizziness, vestibular disorders, cephalic syndrome, hyposmia in 19% of patients. The subjects also had anxiety and depressive disorders according to the HADS scale. Ischemic stroke and transient ischemic attacks (TIA) have been reported in some patients. Pathogenetically justified the feasibility of drugs that affect endothelial function.